STRATEGI GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MENERAPKAN REVISI KURIKULUM 2013 - Ubaedillah Ubaedillah; Asmuni Asmuni; Farihin Nur (Oasis : Jurnal Ilmiah Kajian Islam, 2021)
This research aims to reveal and describe how the strategy of Islamic Education Teachers and Budi Pekerti in implementing the revised Curriculum 2103 in grade III of SDN 1 Sumber Kabupaten Cirebon. This research method uses qualitative methods with a descriptive exploratory approach, exploring and understanding phenomena comprehensively that are directly related to the research subject. The results of this research indicate that the strategy of Islamic Religious Education Teachers and Human Rights in implementing the revised 2013 Curriculum learning in Class III Public Elementary School 1 Sumber Kabupaten Cirebon consists of learning planning strategies and learning implementation strategies. The planning strategy consists of reviewing the curriculum and syllabus, reviewing annual and semester programs and preparing lesson plans (RPP). The implementation of learning strategies includes preliminary activities, main activities and closing activities. The revised 2013 curriculum learning outcomes in class III SDN 1 Sumber can be seen from the results of the daily attitude competency assessment, knowledge and skills. The result shown that the attitude competence as well as knowledge and skill of students are good with an average score is 80.81and 81.74